N-Phenyl-Phthalamic Acid and Fertilization Effects on Flowering, Fruit Set and Fruit Quality of Apple (Malus domestica Borkh.) - Racskó, József (Acta Agraria Debreceniensis, 2006)
On seven apple cultivars (Gala Must, Gloster, Granny Smith, Idared, Jonagold, Jonathan Csány 1, Mutsu), the authors studied the influence of N-phenyl-phthalamic (PPA) acid and fertilization on flowering, fruit set and fruit quality in the years 2003-2004. The research results showed that PPA application extended the flowering time of the most cultivars. Fruit set of apple cultivars increased in many cases when regulator was applied. The additional nutrient supply could increase the fruit set too. The increase of fruit set increased the number of fruit per tree. Quality parameters determined by fertilization and fruit number per tree. For example, when N-phenyl-phthalamic acid was applied without fertilization the fruit number per tree increased considerably however, it caused a considerable frittering away. The reason for this is that fruit set was high and fruit received not enough nutrition for growing up. The skin colour of fruits was decreased in several cases by the treatments. In one respect the enlarged fruit number was shaded the others and the fertilization increased the vegetative shading leaf area.